TERHADAP KINERJA USAHA PEDAGANG KAKI LIMA MENETAP (SUATU SURVAI PADA PUSAT PERDAGANGAN DAN WISATA DI KOTA SURAKARTA) - Mulyanto, Mulyanto (Benefit, 2007)
Endless economic crises that caused the level of society income fallingand the amount of people who live below poverty line is increasing. Economiccrisis has also created company-declining productivity therefore a lotdisconnection of working relationship that caused increasing unemploymenthappened. Enabling informal sector especially cloister merchant is hardlyneeded. The problem of cloister merchant is an interesting topic to study. Thisresearch is aimed to describe the cloister merchant motivations, managerial skill,and the performance of cloister merchant work to manage their business.Analyzing contribution of willing to achieve, risk taking, personal responsibility,searching feedback, new business effort, cooperation, future orientation, willingto work hard indicators. Analyzing contribution of planning skill, decision taking,budgeting, organization, coordinating, coordinating and supervision towardcloister merchant managerial skill indicators. Analyzing output quality, outputquality, working time, and working process toward cloister merchant businessperformance indicators.